Clinic management system : outpatient management system - Nurzety Aqtar, Ahmad Azuan (2005)
As people become more educated, hence people become more aware of the quality of their life especially something that is related toward their health.The poor service in health care would give an effect towards the development of our country to receive a treatment from government hospitals, patients sometimes need to wait for hours.While for administration's task they need to keep track a huge number of filing where all details on patients were being kept,sometimes it leads to data redundancy and an additional workload.That is why Outpatient. Management System is being proposed.Outpatient Management System is develop using a web-based, concept.This system is develop using Java.ServerPages (JSP) and is design using Macromedia Dreamweaver MX .Because Outpatient Management System is a management type of system .thus,.the development of this system is according to the Protocol Management System where this protocol is more like aguideline-in order to develop amanagemenuypeofsystem Outpatient Management System helps Outpatient Department, which are attend by more than 500 hundreds patients each. day perform a better service in term,of registration process, patient's details and reduce time waiting for patients With the existence of this system.the registration process would avoid - data redundancy, records keeping on patient details can be find faster and time waiting for patient before received a treatment from doctor could be. lessen,this is because all manual task that happen in Outpatient Department is being convert to computerized type of system.